Surfacing and vertical behaviour of Atlantic bluefin tuna (Thunnus thynnus) in the Mediterranean Sea: implications for aerial surveys. (26th June 2020) - Bauer, Robert Klaus; Forget, Fabien; Fromentin, Jean-Marc; Capello, Manuela
Abstract: Atlantic bluefin tuna ( Thunnus thynnus ) (ABFT) frequently engage in surface basking and foraging behaviour that makes them detectable from afar. This behaviour is utilized for the development of fisheries-independent abundance indices based on aerial surveys, although changes in the surface-feeding dynamics of ABFT are not yet accounted for. We investigated the daytime surfacing behaviour of ABFT at different temporal and vertical resolutions based on 24 individuals (117–158 cm fork length), tagged with pop-up archival tags in the Gulf of Lion, NW-Mediterranean Sea between 2015 and 2016. The results suggest that ABFT remain usually <2 min continuously within the visible surface (0–1 m) during daytime. ABFT presence in the 0–1 and 0–20 m layers varied over time and between individuals but showed a seasonal decline towards autumn with the breakdown of thermal stratification. Furthermore, the rate of surfacing events was highly correlated with the time spent in the 0–20 m layer. Geolocation estimates confirm a strong site fidelity of ABFT during the aerial survey period (August–October) in the Gulf of Lion. Our results support the choice of the survey region and period, but related indices should account for the seasonality of ABFT surface behaviour [i.e. the time spent in the 0–20 m layer.